2005
DOI: 10.1016/j.amjhyper.2004.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Vascular smooth muscle cell NAD(P)H oxidase activity during the development of hypertension: Effect of angiotensin II and role of insulinlike growth factor-1 receptor transactivation

Abstract: Basal and Ang II-induced NAD(P)H-driven ROS generation are enhanced in VSMCs from SHR during development of hypertension, but not in cells from prehypertensive rats. Transactivation of IGF-1R by Ang II may be important in vascular oxidative excess in the development of hypertension in SHR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 37 publications
3
55
1
Order By: Relevance
“…Our results showed that significantly higher ROS exists in late-passage SMCs compared to low ROS in early passage SMCs, indicating the presence of oxidative stress in higher passage SMCs. Interestingly, stimulation with IGF-1 did not enhance the formation of ROS in either group of VSMC, which is consistent with previous results [36,37]. Mitochondria have been proposed as major sites where oxidative stress take place [53,54].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results showed that significantly higher ROS exists in late-passage SMCs compared to low ROS in early passage SMCs, indicating the presence of oxidative stress in higher passage SMCs. Interestingly, stimulation with IGF-1 did not enhance the formation of ROS in either group of VSMC, which is consistent with previous results [36,37]. Mitochondria have been proposed as major sites where oxidative stress take place [53,54].…”
Section: Discussionsupporting
confidence: 81%
“…However, IGF-1 exposure (10 ng/ml) failed to enhance ROS formation in cells from either the early or late passages. This is in contrast to previously published studies, wherein growth factors, such as insulin and platelet-derived growth factor (PDGF) have been reported to promote ROS formation [36,37].…”
Section: Migration and Proliferation Of Different Passage Vsmcscontrasting
confidence: 54%
“…21 This is consistent with the finding that the activity of the glutathione peroxidase, which protects from oxidative damages, is significantly reduced in kidneys of SHR from the age of 8 week onwards. 22 Besides, obvious cardiac hypertrophy is developed around week 8, for example, together with an activation of the cardiac endothelin system.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, to determine whether K ϩ channel current normalization by GSH o was mediated by a phosphorylation mechanism, the GSH o protocol was repeated after pretreating myocytes from post-MI hearts for 30 min with one of two pan-specific inhibitors of tyrosine kinase: genistein (1 mol/l) or lavendustin A (10 mol/l). We also examined the effect of AG1024 (100 nmol/l), a specific inhibitor of insulin receptor tyrosine kinase (9). As shown in Fig.…”
Section: Signaling Mechanisms Involved In Kmentioning
confidence: 99%